A benzamide‐dependent ftsZ mutant reveals residues crucial for Z‐ring assembly. Issue 6 (22nd December 2015) - Adams, David William; Wu, Ling Juan; Errington, Jeff
Summary: In almost all bacteria, cell division is co‐ordinated by the essential tubulin homologue FtsZ and represents an attractive but as yet unexploited target for new antibiotics. The benzamides, e.g. PC190723, are potent FtsZ inhibitors that have the potential to yield an important new class of antibiotic. However, the evolution of resistance poses a challenge to their development. Here we show that a collection of PC190723‐resistant and ‐dependent strains of S taphylococcus aureus exhibit severe growth and morphological defects, questioning whether these fts Z mutations would be clinically relevant. Importantly, we show that the most commonly isolated substitution remains sensitive to the simplest benzamide 3‐MBA and likely works by occluding compound binding. Extending this analysis to B acillus subtilis, we isolated a novel benzamide‐dependent strain that divides using unusual helical division events. The fts Z mutation responsible encodes the substitution of a highly conserved residue, which lies outside the benzamide‐binding site and forms part of an interface between the N‐ and C‐terminal domains that we show is necessary for normal FtsZ function. Together with an intragenic suppressor mutation that mimics benzamide binding, the results provide genetic evidence that benzamides restrict conformational changes in FtsZ and also highlights their utility as tools to probe bacterial division. Abstract : Bacterial cell division is an attractive target for new antibiotics. The benzamides are a novel class of antibacterial that target the essential cell division protein FtsZ. Here we investigated the effects of benzamide‐resistance conferring ftsZ mutations and have isolated an unusual mutant that is benzamide‐dependent for division and divides in a helical manner. In the absence of benzamide division is blocked at the transition between FtsZ polymer formation and full Z‐ring assembly.